Hubungan Dukungan Keluarga dengan Keaktifan Lansia dalam Mengikuti Posyandu Lansia di Gampong Lambro Bileu Wilayah Kerja Puskesmas Kuta Baro Aceh Besar - Mardayanti Zega; Nurul Sakdah; Kiki Rezeki Amelia (Lembaga Pengembangan Kinerja Dosen, 2025)
The activeness of the elderly in participating in posyandu (integrated health post) activities remains a problem in various regions across Indonesia. The low level of participation is often caused by a lack of family support and the physical limitations faced by elderly individuals. In fact, posyandu for the elderly plays a crucial role in health monitoring, disease prevention, and improving the overall quality of life in old age. Through posyandu, elderly people can receive regular health check-ups, nutritional education, and guidance to maintain both physical and mental well-being. This study employed a descriptive correlational design with a cross-sectional approach. The population consisted of all elderly residents of Gampong Lambro Bileu, totaling 58 participants, all of whom were included as a total sample. The research was carried out from May 28 to June 11, 2025, within the working area of Kuta Baro Health Center, Aceh Besar. Data collection instruments included a family support questionnaire with 10 positive statements and an elderly posyandu attendance sheet covering the last six months. Data were analyzed using univariate and bivariate analysis with the Chi-Square test to determine relationships between variables. The findings indicated that most elderly individuals who received strong family support were very active in attending posyandu activities. The p-value of 0.024 showed a significant relationship between family support and the activeness of the elderly in participating in posyandu (p < 0.05). Therefore, families are encouraged to be more involved in accompanying, motivating, and supporting the elderly to stay active in posyandu for better health and quality of life.